042 Determinants of baseline disability in relapsing remitting multiple sclerosis. Issue 6 (27th May 2022) - Brown, Fraser; Kearns, Patrick; Martin, Sarah-Jane; Connick, Peter; Hunt, David; Chandran, Siddharthan
Abstract : Background: Determinants of multiple sclerosis aetiology and natural history remain unknown. Objectives: To determine factors associated with level of disability measured by Expanded Disability Severity Scale (EDSS) and Multiple Sclerosis Functional Composite (MSFC) in patients newly diagnosed with relapsing-remitting multiple sclerosis (RRMS). Methods: We collected demographic, clinical, smoking and alcohol history in an incidence cohort of patients with RRMS recruited within six months of diagnosis. Ordinal logistic regression was used to examine association of EDSS with clinical and demographic features. Linear regression was used to examine asso- ciation between the same variables and MSFC. Results: We recruited 440 patients. Mean age at onset was 33.61 and 75.9% were female. Age at onset was shown to be associated with higher disability as measured by EDSS and MSFC. Sex was not signifi- cantly associated with outcome. After adjustment for age and sex, time to diagnosis, current smoking, having ever smoked and obesity were associated with higher EDSS whereas having ever smoked were associated with worse MSFC scores. Conclusions: Disability in relapsing-remitting multiple sclerosis is partly determined by demographic features and modifiable risk factors even early in disease course. Much of the variation remains to be elucidated and individualised risk prediction is an unmet need. fraser@tonnard.co.uk